Management of exposed collagen membrane after socket seal surgery for placement of dental implant - Prasad Nadig (Advances in Human Biology, 2017)
The predictable success of dental implants has revolutionised dentistry in many ways. Clinicians are becoming more vigilant in planning teeth extraction than ever before. This has led to the routine use of the concept of the socket preservation after tooth extraction and before the placement of dental implant. This routine use of collagen membrane use for socket preservation has uncovered a new situation of the exposed collagen membrane left intentionally or unintentionally which has to be dealt with frequently. The management of such exposed collagen membrane becomes vital for the success of socket seal surgery. This case report emphasises on the management of exposed collagen membrane after socket seal surgery and before placement of dental implant.